Hubungan Antara Percaya Diri Dengan Kemampuan Melakukan Gerakan Lompat Harimau Pada Mahasiswa Tahun Akademik 2020 Penjaskesrek FKIP - Tuhulele, Rizki; Hasbullah, Bahmid; Matitaputty, Johanna (MANGGUREBE: Journal Physical Education, Health and Recreation, 2023)
This study aims to find out whether there is a relationship between self-confidence and the ability to perform tiger jump movements in students of Academic Year 2020 FKIP Unpatti, the research project used is the research plan X and Y, the sample in this study is 40 students of the academic year 2020 who can do tiger jumps. The variable in the study is confidence represented by the variable X and the skill to jump tiger represented with variable Y. The test results of the research data through the statistical test showed that the score (0,864) was greater than that of the table (0,312) at a significant level of 0.05%, thus the results of this study show that there was a significant relationship between confidence and ability to do the jump of tiger in academic students in the year 2020.